Junípero Serra’s Canonization or Eurocentric Heteronomy - Welizarowicz, Grzegorz (Studia Anglica Posnaniensia, 2018)
The article assesses the recent canonization of Junípero Serra, Spanish Franciscan missionary and founder of the California mission system. I begin by introducing the priest and outlining the genesis of his assignment. I then discuss the model of missions’ operation and problematize their results. The rise of Serra’s legend is situated within the historical context of California’s “fantasy heritage”. I later outline the chief arguments and metaphors mobilized by the Church in support of the new saint. In the central part of the essay, I address and critically examine the ramifications of a document Serra authored and which the Church took as the priest’s passport to sainthood. I argue that the document inaugurated the epistemic and social divides in California and, marking the Indian as homo sacer (Agamben), paved the way to the Indigenous genocide in the mission and American eras. Following this, I offer a semiological (after Barthes and Lakoff) interpretation of the canonization as a modern myth, argue that metaphors invoked in support of the priest inverted the historical role played by Serra and, finally, ponder the moral ramifications of this canonization.